INVESTIGATION ABOUT COMPLAINT MANAGEMENT, PRODUCT DESIGN, AND PERCEIVED QUALITY AFFECTING CONSUMER REPURCHASE INTENTION OF XIAOMI SMARTPHONE PRODUCT IN MANADO CITY - Badiangsie, Luis; Lapian, Joyce S.L.H.V.; Tumbuan, Willem J.F. Alfa (Universitas Sam Ratulangi, 2019)
Xiaomi smartphone market share are increase 22% from second quarter of 2017 to second quarter of 2018 and become the most increase smartphone product market share. Consumer repurchase intention is about the consumer attitude toward the product that make them want to repurchase after have an experience of using those product. Consumer repurchase intention can be influence by some factors, complaint management, product design, and perceived quality. The aim of this study is to know the simultaneous and partial influence of complaint management, product design, and perceived product quality toward consumer repurchase intention of Xiaomi smartphone in Manado city. This research used multiple regression analysis with sample of 100 respondents. The result shows that complaint management, product design, and perceived product quality has a significant influence toward consumer repurchase intention of Xiaomi smartphone simultaneously and partially. The customers who are satisfied with the complaint management, design, and existing product quality are encouraged to repurchase the product. Also, company should seek to build products based on the concepts of value innovation in order to create value for the customers by improving the aspects of the complaint management and product design.Â Keywords: repurchase intention, complaint management, product design, perceived qualityÂ